Laparoscopic Approach for Management of Hydatid Cyst of Liver - Shrestha, Suman Kumar; Thapa, Prabin Bikram; Maharjan, Dhiresh Kumar; Tamang, Tseten Yonjan (Journal of Nepal Health Research Council, 2017)
Background: Laparoscopy surgery trials are small and unconvincing at present and are limited to higher centers. The objective of the study is to determine the clinical features, prevalence of site of hydatid cyst and complications of this modality of this treatment. Methods: A cross sectional study was carried out in all patients with one or two hepatic hydatid cyst who underwent laparoscopic management in KMCTH from January 2013 to March 2015 were included in the study. Aspiration, deroofing and evacuation of the hydatid cyst were done. Results: Twenty six patients underwent laparoscopic management for liver hydatid cysts. Males were seven (65.38%) and females were 9(34.61%).The mean age was 35.5±13.1 years (range 21-55years.) The commonest complaint was pain and discomfort in 13(50%) patients and lump in 6(13.06%) patients. Twenty four (92.3%) patients were successfully treated with laparoscopic approach. Two (7.69%) patients had to be converted to laparotomy because of dense adhesions and bleeding. Mean operation time was 43.6±10.6 minutes. Two (7.69%) patients had port site infection. One (3.84%) patient had bile leak and no recurrence and mortality in our series. Conclusions: Laparoscopic management of liver hydatid cyst was safe and effective in selective group of patients in equipped hospital.